On the dynamics of unemployment and wage distributions - Jean-Marc Robin (Centre for Microdata Methods and Practice (cemmap), 2010)
Postel-Vinay and Robin' (2002) sequential auction model is extended to allow for aggregate productivity shocks. Workers exhibit permanent differences in ability while firms are identical. Negative aggregate productivity shocks induce job destruction by driving the surplus of matches with low ability workers to negative values. Endogenous job destruction coupled with worker heterogeneity thus provides a mechanism for amplifying productivity shocks that offers an original solution to the unemployment volatility puzzle (Shimer, 2005). Moreover, positive or negative shocks may lead employers and employees to renegotiate low wages up and high wages down when agents' individual surpluses become negative. The model delivers rich business cycle dynamics of wage distributions and explains why both low wages and high wages are more procyclical than wages in the middle of the distribution and why wage inequality may be countercyclical, as the data seem to suggest is true.
Keywords: 330; Lohnstruktur; Produktivität; Konjunktur; Theorie der Arbeitslosigkeit; Lohntheorie; Dynamisches Gleichgewicht; Auktion; Theorie; USA